Generation and Construction of Professional Identity Género y construcción de identidad profesional - Sonsoles San Ramon Gago (Arizona State University, 2001)
It is my aim in this article to carry out a thorough examination of the basic elements, ideology and symbolic representations which constitute the identity of a generation of schoolmistresses belonging to a crucial period in Spanish history: that of the intermediate Francoism, during the process of modernization which took place at the end of the 1950s. The investigation is based on live testimonies of schoolmistresses between the ages of 65 and 70. First, I will point out the antecedents of the profession of schoolmistress in Spain and show how circumstances made her role gradually and increasingly more important. Then I will reveal what kinds of opposition and obstacles schoolmistresses came up against and had to overcome in order to obtain professional equality with male colleagues. Finally, I will contextualize and interpret, in cultural terms, the attitudes, images and motivations, which turned out to be very symbolic, that arose during the interviews with these women. This article, which fills a large gap in research on this subject, concentrates on a very particular and decisive moment. It is my intention to invite the reader to reflect on a social phenomenon of great importance today: that of the feminization of teaching, which can be seen in most countries and whose influence can be observed, not only in a country´s educational system, but in the economic, political, religious and cultural spheres as well. Mi propósito en este artículo es profundizar, mediante el análisis de testimonios vivos de maestras en edades comprendidas entre 65 y 70 años, en los elementos básicos, discursos ideológicos y representaciones simbólicas, que constituyen la identidad de una generación de maestras situadas en un contexto histórico clave para la historia de mi país: el franquismo intermedio, que tiene lugar en el proceso de la modernización que se produce en el paso de los años 50 a los 60. Con la intención de introducir al lector en el tema, comenzaré por señalar los antecedentes de la profesión de maestra en España. Una vez explicadas las circunstancias que propiciaron la línea ascendente hacia la profesionalización de la maestra, y después de señalar los obstáculos que debió vencer hasta conseguir su equiparación profesional con el maestro, pasaré a contextualizar e interpretar, en términos culturales, las actitudes, imágenes y motivaciones que han ido apareciendo, cargadas de valor simbólico, en la marcha del discurso de las maestras. Este artículo, que viene así a cubrir una laguna de investigación en España, enfocada además en un período muy particular y determinante, pretende invitar al lector a reflexionar sobre un fenómeno social de máxima actualidad: el de la feminización docente, visible en la mayoría de los países, que salpica, más allá del espacio educativo, a los ámbitos económicos, políticos, religiosos y culturales de un país.